2010
DOI: 10.1007/s00044-010-9532-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of a novel class as antileishmanial agent

Abstract: Leishmaniases are a group of diseases caused by the protozoan parasites of the genus Leishmania. Despite the tremendous progress made in the understanding of the biochemistry and molecular biology of the parasite, the first choice treatment for leishmaniases still relies on pentavalent antimonial developed more than 50 years ago. These drugs are potentially toxic and often ineffective. The spread of drug resistance, combined with other shortcoming of the available antileishmanial drugs, emphasizes the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These compounds comprising a diverse group of chemical structures have been reported as antileishmanial agents. Most of them include nitrogen heterocycle rings such as quinolines 9 , quinazolines 10 , acridines 11 , pyrimidines 12 , pyrazols 13 , pyridines 8 , benzothiazoles 14 , imidazoles 15 , thiadiazoles 16 and include functional structures such as alkyl phospholipids 17 , ether phospholipids 18 , chalcones 19 , amidines 20 , oximes 21 , amidoxime 22 , hydrazones 23 and hydrazides 24,25 . On the other hand, a number of quaternized amine derivatives such as thiadiazolium-phenylamine 26,27 , arylisoquinolinium 28 , imidazo-pyridinium 29 , alkylammonium-phenothiazines 30 , indolo-quinolinium 31 and naphthalimide-amonnium 32 were previously reported to exert antiprotozoal properties.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds comprising a diverse group of chemical structures have been reported as antileishmanial agents. Most of them include nitrogen heterocycle rings such as quinolines 9 , quinazolines 10 , acridines 11 , pyrimidines 12 , pyrazols 13 , pyridines 8 , benzothiazoles 14 , imidazoles 15 , thiadiazoles 16 and include functional structures such as alkyl phospholipids 17 , ether phospholipids 18 , chalcones 19 , amidines 20 , oximes 21 , amidoxime 22 , hydrazones 23 and hydrazides 24,25 . On the other hand, a number of quaternized amine derivatives such as thiadiazolium-phenylamine 26,27 , arylisoquinolinium 28 , imidazo-pyridinium 29 , alkylammonium-phenothiazines 30 , indolo-quinolinium 31 and naphthalimide-amonnium 32 were previously reported to exert antiprotozoal properties.…”
Section: Introductionmentioning
confidence: 99%
“…41) Saudi et al identified nine urea and thiourea derivatives with antileishmanial activity in vitro (L. major promastigotes), and four of them also showed in vivo activity. 42) Among 31 monosubstituted thiourea derivatives which showed promastigote IC 50 values above 100 µM Boechat described three derivatives which were more than 50-fold less active than pentamidine against L. amazonensis promastigotes and were not tested against amastigotes. In addition, authors proposed the enzyme arginase as a supposed target for those compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-based heterocycles are privileged medicinal structures with valuable pharmacological properties. Besides previous reports on the antileishmanial activity of similar nitrogen-containing compounds such as quinazolines ( 11 ), a few dihydropyrimidinone (DHPM) derivatives were also reported to exhibit antileishmanial activities ( 12 13 14 ). To our best knowledge, previous reports mostly included DHPMs with 5-carboxylate ( 12 ), 5- alkanoyl ( 14 ), or 5-hyetroatyl ( 15 ) moieties.…”
Section: Introductionmentioning
confidence: 90%
“…To our best knowledge, previous reports mostly included DHPMs with 5-carboxylate ( 12 ), 5- alkanoyl ( 14 ), or 5-hyetroatyl ( 15 ) moieties. Fewer studies were dedicated to the antileishmanial activities of 5-carboxamide substituents and within this category, some aliphatic carboxamide derivatives were demonstrated to possess antileishmanial effects ( 13 ).…”
Section: Introductionmentioning
confidence: 99%